The effect of providing climate and health information on support for alternative electricity portfolios. (12th February 2018) - Sergi, Brian; Davis, Alex; Azevedo, Inês
Abstract: Support for addressing climate change and air pollution may depend on the type of information provided to the public. We conduct a discrete choice survey assessing preferences for combinations of electricity generation portfolios, electricity bills, and emissions reductions. We test how participants' preferences change when emissions information is explicitly provided to them. We find that support for climate mitigation increases when mitigation is accompanied by improvements to air quality and human health. We estimate that an average respondent would accept an increase of 19%–27% in their electricity bill if shown information stating that either CO2 or SO2 emissions are reduced by 30%. Furthermore, an average respondent is willing to pay an increase of 30%–40% in electricity bills when shown information stating that both pollutants are reduced by 30% simultaneously. Our findings suggest that the type of emissions information provided to the public will affect their support for different electricity portfolios.